Peningkatan Efisiensi Operasional Commuter Line Jogja-Solo Melalui Perbaikan Jadwal - Putri, Ananda Agneshia; Oktavianto, Alfin; Pamursari, Nurmagita; Sari, Nurwanda (PendIPA Journal of Science Education, 2024)
The Commuter Line is a train service that serves short routes within or between cities, mainly for daily commuters in urban areas. Launched on February 10, 2021 to replace KRD Prameks, KRL Jogja-Solo aims to improve the efficiency of intercity travel. Passenger numbers for KRL Jogja-Solo continue to increase, based on PT KAI Commuter Line's latest data, with passenger numbers per month in 2023 showing a significant increase. For example, in August there were 512,547 passengers, while in December it increased to 709,634 passengers. This increase creates pressure on the existing carrying capacity. This research aims to assess the challenges faced by KRL Jogja-Solo in accommodating the increasing number of passengers and find solutions to meet the growing demand. This research focuses on improving the operational efficiency of KRL Jogja-Solo through schedule improvements, assessing passenger volume, cross capacity, and passenger projections for the period 2024-2033. The Scott method is used for cross capacity analysis and the geometric growth formula for passenger projections, with optimal solutions based on optimistic, moderate, and pessimistic scenarios. Results show that the addition of four afternoon trips and skip-stop scheme is the best solution in the optimistic scenario, skip-stop scheme without additional trips in the moderate scenario, and improvement of the existing schedule in the pessimistic scenario. This research emphasizes the importance of long-term planning and regular evaluation to ensure the smoothness and convenience of the Jogja-Solo KRL service.